Association Between Serum Lactate and Unsatisfactory Outcomes in Critically Ill Children in the Immediate Post-operative Period of Liver Transplantation - Fernández-Sarmiento, Jaime; Wilches-Cuadros, María Angélica; Hernandez-Sarmiento, Ricardo; Mulett, Hernando; Moreno-Medina, Karen; Molano, Nicolás; Dominguez, Julián Augusto Palomar; Acevedo, Lorena; Salinas, Claudia; Rivera, Jairo (Frontiers in Pediatrics, 2022)
Objectives: Serum lactate is a useful biomarker of tissue perfusion in critically ill patients. We evaluated the behavior of serum lactate in children in the pediatric intensive care unit (PICU) immediately after liver transplantation and its association with surgical complications, graft dysfunction and 90-day mortality. Materials and methods: A prospective observational study carried out between November 2009 and December 2019. Multidisciplinary PICU at the University Children´s Hospital, Fundación Cardioinfantil-IC, Bogotá, Colombia. Measurements and Main Results: Patients between 1 month and 18 years of age who were in the immediate postoperative period following living-donor or cadaveric liver transplantation were included. A total of 145 patients with a median age of 14 months (IQR 8-60) met the inclusion criteria. Biliary atresia was the main diagnosis in 56.5% of the cases. A serum lactate level greater than 3.0 mmol/L on admission to the PICU was associated with biliary complications (AUC 0.73 95% CI 0.54-0.93; p=0.05) and mortality (AUC 0.72 95% CI 0.63-0.8; p=0.01). A lactate level greater than 2 mmol/L after six hours in the PICU was associated with mortality (AUC 0.70 95% CI 0.54-0.83; p=0.02). Higher lactate levels and lack of clearance were associated with the presence of tardus et parvus waveforms (p=0.001) on liver Doppler, primary dysfunction (p<0.001), arterial thrombosis (p<0.001) and neurological complications (p=0.04). There was an inverse correlation between admission lactate and the volume of fluids administered during surgery (rho=0.36; p<0.001). A total procedure time greater than 350 minutes, along with a vasopressor score greater than 7 and elevated lactate, were associated with worse outcomes (p<0.001). Conclusions: In postoperative pediatric liver transplant patients, the level of serum lactate is associated with postoperative surgical complications and mortality.